Implementasi Nilai Al-Mas’uliyyah Terhadap Dampak Sosial Peternakan Ayam Ras Petelur: Studi Pada PT Padang Jaya Farm Kabupaten Bengkulu Utara - Fitri Indah Lestari; Desi Isnaini; Makmur . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of al-mas'uliyyah (responsibility) values ​​in the management of PT Padang Jaya Farm's laying hen farm, assess the social impact on the surrounding community, and identify factors that support and hinder its implementation in business operational practices. The focus of the study covers four dimensions of al-mas'uliyyah values, namely mas'uliyyah diniyyah (religious), akhlaqiyyah (moral-ethical), ijtima'iyyah (social), and qanuniyyah (regulative). This study uses a qualitative approach with a descriptive method. Data collection was carried out through in-depth interviews with the owner, and the surrounding community, direct observation of the farm's operational business activities, and documentation in the form of activity photos. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of al-mas'uliyyah values ​​at PT Padang Jaya Farm is not optimal and integrated. The values ​​of social justice (mas'uliyyah diniyyah) and ijtima'iyyah (ijtima'iyyah) have been implemented quite well, while the values ​​of morality (mas'uliyyah akhlaqiyyah) and qanuniyyah (qanuniyyah) have not yet been implemented optimally, particularly in environmental impact management and compliance with regulations, which are still administrative in nature.